Wedding / Contest The Royal Ballet's Stravinsky revivals viewed - Robertson, Allen (Dance Books Ltd., Alton,Hampshire (UK), 2001)
The Royal Ballet's Stravinsky revivals viewed. This is great choreography brushed off, dusted down, breathing and alive. PALABRAS CLAVE: Patricia Neary, Christopher Newton, Les Noces, Agon, Royal Ballet, Igor Stravinsky.